(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study was designed to examine the relationship between Emotional Intelligence and Organizational Performance in commercial banks in Uyo Metropolis of Akwa Ibom State. A cross-sectional survey was adopted for the study and a sample of 162 respondents was drawn from the population of 271 using Taro Yamane’s scientific sampling technique. For the objectives of the study to be achieved, two hypotheses were formulated and tested. The study utilized structured questionnaire and interview as the major instruments for data collection. 162 questionnaires were distributed and 135 were returned. Data were collected and analyzed using simple percentage and ordinal logistic regression. Results showed that there is a significant and positive relationship between variables of emotional intelligence such as self-control, self-management and, and employee performance in commercial banks in Uyo Metropolis of Akwa Ibom State. It was recommended that, self-control should be sustained by bank employees by continually developing the capacity to alter their thoughts, feelings, and behaviors to align them with organizational goals to enhance performance as well as developing the capacity to manage emotions as one of the major determinants of harmonious relationship among members in an organization.